The Power of No - Abbie Headon (Ilex Press Ltd, 2019)
Say yes to no. No more confidence knocks, no more overwhelming workloads and no more hesitation. By using this single word and canny bible you will break the taboo that surrounds no and come to understand your own needs.The Power of NO teaches you to value your time and equips you with the know-how to set your own rules, find direction and demand respec...